2010
DOI: 10.1086/656591
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Effect of Screening Orthopedic Surgery Patients Preoperatively for Methicillin-ResistantStaphylococcus aureus

Abstract: BACKGROUND AND OBJECTIVE Patients undergoing orthopedic surgery are susceptible to methicillin-resistant Staphylococcus aureus (MRSA) infections, which can result in increased morbidity, hospital lengths of stay, and medical costs. We sought to estimate the economic value of routine preoperative MRSA screening and decolonization of orthopedic surgery patients. METHODS A stochastic decision-analytic computer simulation model was used to evaluate the economic value of implementing this strategy (compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 53 publications
(33 reference statements)
0
37
0
4
Order By: Relevance
“…Lee et al [34] showed that screening and decolonization was still the most cost-effective choice even when the following parameters were changed to make the protocol less desirable: a second body site was screened, there was a low prevalence of MRSA, and the decolonization success rates were low. Studies in orthopaedic patients [22,36,52] and those having total joint arthroplasty [19,42,43] also showed that implementing a S. aureus screening and decolonization protocol resulted in cost savings, because the cost of treating patients with SSIs with readmission was greater than the costs of instituting the screening and treatment protocol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [34] showed that screening and decolonization was still the most cost-effective choice even when the following parameters were changed to make the protocol less desirable: a second body site was screened, there was a low prevalence of MRSA, and the decolonization success rates were low. Studies in orthopaedic patients [22,36,52] and those having total joint arthroplasty [19,42,43] also showed that implementing a S. aureus screening and decolonization protocol resulted in cost savings, because the cost of treating patients with SSIs with readmission was greater than the costs of instituting the screening and treatment protocol.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies (Table 3) examined the cost of implementing a S. aureus screening and decolonization protocol [10,19,22,34,36,42,43,48,52,55]. The method of evaluating costs differed among studies, because four of the studies were based on economic models [10,34,48,55], whereas ITT = intention to treat; MSSA = methicillin-sensitive S. aureus; MRSA = methicillin-resistant S. aureus; RCT = randomized controlled trial; RR = relative risk; SSI = surgical site infection.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…However, this model was based on data from a hospital in Geneva, which may have lower rates of MRSA colonization than U.S. hospitals. Conversely, using data inputs from the United States, multiple studies found that MRSA screening and decolonization prior to cardiac, vascular, or orthopedic surgery or heartlung transplant was cost-effective from the third-party payer perspective and the hospital perspective (50,(157)(158)(159)(160)(161). However, Lee et al, found that screening and decolonization of pregnant women prior to cesarean delivery were not cost-effective (162).…”
Section: Economic Viabilitymentioning
confidence: 99%
“…Although screening and targeted decolonization of patients may not be as effective as universal decolonization, studies have demonstrated that sensitive detection of MRSA can significantly reduce the rate of postsurgical infection by identifying those patients who will benefit from preoperative prophylaxis and decolonization (21,22). As a result, reduced rates of postsurgical infection resulting from molecular screening methods have been shown to reduce the cost of health care to both the hospital and third-party payer (23). Likewise, rapid and accurate detection of MRSA, vancomycin-resistant Enterococcus (VRE), or carbapenem-resistant Enterobacteriaceae (CRE) may aid infection control efforts by identifying those patients requiring contact isolation.…”
Section: Singleplex Nucleic Acid Testsmentioning
confidence: 99%